Screening of SARS-CoV-2 among homeless people, asylum-seekers and other people living in precarious conditions in Marseille, France, March–April 2020 - Tran Duc Anh Ly; Nhu Ngoc Nguyen; Van Thuan Hoang; Ndiaw Goumballa; Meriem Louni; Naomie Canard; Thi Loi Dao; Hacene Medkour; Audrey Borg; Kevin Bardy; Véra Esteves-Vieira; Véronique Filosa; et al. (International Journal of Infectious Diseases, 2021)
Background: Surveillance of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection among sheltered homeless and other vulnerable people might provide the information needed to prevent its spread within accommodation centres. Methods: Data were obtained from 698 participants in different accommodation centres (411 homeless individuals, 77 asylum-seekers, 58 other people living in precarious conditions and 152 employees working in these accommodation centres) who completed questionnaires and had nasal samples collected between 26 March and 17 April 2020. SARS-CoV-2 carriage was assessed by quantitative PCR. Results: We found a high acceptance rate (78.9%) for testing. Overall, 49 people (7.0%) were positive for SARS-CoV-2, including 37 homeless individuals (of 411, 9.0%) and 12 employees (of 152, 7.9%). SARS-CoV-2 positivity correlated with symptoms, although 51% of patients who tested positive did not report respiratory symptoms or fever. Among homeless people, being young (18–34 years) (odds ratio 3.83, 95% confidence interval 1.47–10.0, p = 0.006) and being housed in one specific shelter (odds ratio 9.13, 95% confidence interval 4.09–20.37, p < 0.001) were independent factors associated with SARS-CoV-2 positivity (rates of 11.4% and 20.6%, respectively). Discussion: Symptom screening alone is insufficient to prevent SARS-CoV-2 transmission in vulnerable sheltered people. Systematic testing should be promoted.